EFFECT OF CROPPING SYSTEMS, FERTILITY LEVELS AND MOISTURE CONSERVATION PRACTICES ON GROWTH AND YIELD OF PEARLMILLET AND MOTHBEAN IN INTERCROPPING SYSTEM - TETARWAL, J.P.; RANA, K.S. (Annals of Agricultural Research, 2014)
A field experiment on moisture conservation and nutrient management studies in sole and intercropped pearlmillet under rainfed conditions was conducted during two consecutive kharif seasons of 2003 and 2004. The treatment combination comprised two cropping systems and three fertility levels in main plots and four moisture conservation practices. The results indicated that planting of one row of mothbean in between paired rows (30/70cm) of pearlmillet was superior over sole pearlmillet in respect of pearlmillet equivalent yield. Application of 40 kg N + 20 kg P2O5/ ha recorded higher growth and yield of pearlmillet under both sole and intercropping system as well as that of mothbean. Application of FYM @ 5t/ha + dust mulch + straw mulch was found the best moisture conservation practice by recording higher growth and yield of pearlmillet as well as mothbean over rest of the moisture conservation practices.